Job Uncertainty After Ph.D.: A Common Concern for Doctoral Students of Technical Institutes of North East India - Meetei, Loitongbam Athouba; Singh, N. B.; Sarma, Tridib; Mutum, Kelvin (Prabandhan: Indian Journal of Management, 2019)
A doctoral degree is the highest level of academic degree awarded by an academic institute. The doctoral program not only prepares the workforce to become faculties, administrators, and researchers in an academic institute, but also prepares the workforce for industry and business organizations. These workforces play a very important role in developing innovation that drives the economic growth of a nation. Attrition of doctoral students potentially wastes resources and time of both faculties and students which could otherwise be utilized elsewhere. High attrition reduces research output, which is an important factor while evaluating the status of an institution. Limited numbers of studies have been done on doctoral students' satisfaction and attrition in India. The present study was an attempt to explore the experience of doctoral students and also to find the factors influencing satisfaction of doctoral students studying in technical institutes of North East India. An offline survey was conducted with 300 doctoral students studying Engineering, Science, Mathematics, and Humanities & Management. Data collected were analyzed using factor analysis and hierarchical multiple regression. Supervisor/Guide and Department Support, Reason for Doing Ph.D., Stress and Lack of Motivation, and Insecurity were found to contribute 41% to doctoral students' satisfaction with a p-value of 0.039. The doctoral students studying in different departments had a common fear of not getting a matching job after Ph.D.